2020
DOI: 10.21776/ub.jam.2020.018.01.19
|View full text |Cite
|
Sign up to set email alerts
|

Customer Loyalty, Through Customer Satisfaction in Customers Pt. Xyz

Abstract: PT. XYZ is one paper company in East Java, Indonesia. The paper industry grows much wider opportunities to consumers to help select and purchase the product in accordance with the wishes and needs. This resulted in the emergence of competition between paper companies. Consumer expectations this time are getting a good paper and an affordable price, if these expectations are fulfilled then the customer will feel satisfied and by itself will refer to the paper company. PT. XYZ as the paper industry players feel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
2
7
1
3
Order By: Relevance
“…We also evaluated the mediating effect of trust between e-customer satisfaction and e-customer loyalty, which confirmed the mediation of trust between ECS and ECL. The results of the current study are consistent with preceding studies, such as Hayati et al (2020), Dewi and Surabaya (2020), Mayer et al (1995), Fang et al (2011), Palvia (2009, Kim et al (2009), Ahmed et al (2017), Ali and Raza (2017), Godwin et al (2010), Dimitriadis et al (2011), Ahmad and Al-Zubi (2011), and Crumlish and Malone (2009. We also incorporated religiosity as a mediator in our considered modified E-S-QUAL model.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We also evaluated the mediating effect of trust between e-customer satisfaction and e-customer loyalty, which confirmed the mediation of trust between ECS and ECL. The results of the current study are consistent with preceding studies, such as Hayati et al (2020), Dewi and Surabaya (2020), Mayer et al (1995), Fang et al (2011), Palvia (2009, Kim et al (2009), Ahmed et al (2017), Ali and Raza (2017), Godwin et al (2010), Dimitriadis et al (2011), Ahmad and Al-Zubi (2011), and Crumlish and Malone (2009. We also incorporated religiosity as a mediator in our considered modified E-S-QUAL model.…”
Section: Discussionsupporting
confidence: 93%
“…Previous literature emphasized the importance of Islamic e-banking as it permits customers can do transactions 24/7 without any hindrances by observing Islamic Laws. According to Boateng et al (2021), Butt (2018), Iqbal (2020), Dewi and Surabaya (2020), and Nguyen and Leblanc (2002), ecustomer loyalty increases when customer frequently uses e-banking services with satisfaction. Hence, it demonstrated that e-customer satisfaction is directly associated with ecustomer loyalty.…”
Section: E-customers Loyaltymentioning
confidence: 99%
See 2 more Smart Citations
“…Satisfaction is feeling or behavior when purchasing or using a service or product from a company to fulfill user expectations. Satisfaction plays a significant role in a company when facing market competition [9].…”
Section: E Satisfactionmentioning
confidence: 99%